2005
DOI: 10.1161/01.atv.0000148324.63685.6a
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Elevated Liver Enzymes and C-Reactive Protein

Abstract: Objective-The objective of this study was to test whether the frequent association between liver enzyme elevations and various components of the metabolic syndrome is associated with higher C-reactive protein (CRP) levels. Methods and Results-Alanine aminotransferase (ALT), alkaline phosphatase (Alk-P), and high-sensitivity CRP were measured in 1740 subjects. Adjusted geometric mean CRP was calculated for subjects with normal and elevated ALT and for subjects with normal and elevated Alk-P, adjusting for age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(86 citation statements)
references
References 44 publications
1
84
1
Order By: Relevance
“…A positive correlation between CRP/IL-6 and TG concentrations exists (Fredrikson et al, 2004). Dietary carbohydrates stimulate TG production in the liver and may cause secondary hepatic inflammation with associated higher CRP concentrations (Kerner et al, 2005). This increase in TG seems to be intermittent and the concentrations decrease again over time indicating that DF might counteract the hypertriglyceridaemic effect of carbohydrates (Rivellese et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation between CRP/IL-6 and TG concentrations exists (Fredrikson et al, 2004). Dietary carbohydrates stimulate TG production in the liver and may cause secondary hepatic inflammation with associated higher CRP concentrations (Kerner et al, 2005). This increase in TG seems to be intermittent and the concentrations decrease again over time indicating that DF might counteract the hypertriglyceridaemic effect of carbohydrates (Rivellese et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Levamisole, a nonspecific inhibitor of ALP, could also reduce aortic calcification of uremic rat (17). Apart from vascular calcification, previous studies suggested that inflammation indicated by a higher level of CRP or the counts of white blood cells might be associated with elevated ALP and then participate in higher mortality (3,20,21). N/L is widely used as a marker of inflammation and a strong predictor for overall and cardiovascular mortality in PD patients (22).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated C-reactive protein (CRP) concentrations are related to insulin resistance, to MS, predict coronary heart disease, diabetes and have also been reported in NAFLD. 16,17 A high prevalence of nonorgan-specific autoantibodies, has been found in NAFLD associated with insulin resistance 18 and in patients with coronary atherosclerosis as well. 19 These data indicate that systemic subclinical inflammation typically associated with MS are also found in NAFLD.…”
Section: Pathogenesismentioning
confidence: 99%